2010
DOI: 10.1007/s10522-010-9269-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in some oxidative stress-related genetic diseases: Ataxia-Telangiectasia, Down Syndrome, Fanconi Anaemia and Werner Syndrome

Abstract: Oxidative stress is a phenotypic hallmark in several genetic disorders characterized by cancer predisposition and/or propensity to premature ageing. Here we review the published evidence for the involvement of oxidative stress in the phenotypes of Ataxia-Telangiectasia (A-T), Down Syndrome (DS), Fanconi Anaemia (FA), and Werner Syndrome (WS), from the viewpoint of mitochondrial dysfunction. Mitochondria are recognized as both the cell compartment where energetic metabolism occurs and as the first and most susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 153 publications
3
86
0
1
Order By: Relevance
“…Indeed, knockdown of either ATM or G6PD in the context of FLT3 inhibition caused further decreases in intracellular glucose and glutamine, major sources for central carbon metabolism. It has previously been shown that a proportion of ATM is localized in the mitochondria and that ATM deficiency is associated with increased mitochondrial ROS (16)(17)(18), consistent with our data from AML cells. Together, these results suggest a model in which ATM acts as a sentinel for mitochondrial ROS, activating G6PD and the PPP when ROS levels become excessive, such as on FLT3 inhibition, to quell oxidative stress through up-regulation of glutathione metabolism and possibly other pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, knockdown of either ATM or G6PD in the context of FLT3 inhibition caused further decreases in intracellular glucose and glutamine, major sources for central carbon metabolism. It has previously been shown that a proportion of ATM is localized in the mitochondria and that ATM deficiency is associated with increased mitochondrial ROS (16)(17)(18), consistent with our data from AML cells. Together, these results suggest a model in which ATM acts as a sentinel for mitochondrial ROS, activating G6PD and the PPP when ROS levels become excessive, such as on FLT3 inhibition, to quell oxidative stress through up-regulation of glutathione metabolism and possibly other pathways.…”
Section: Discussionsupporting
confidence: 92%
“…It is unknown if our finding of slower lymphocyte respiration in trisomy 21 children is applicable to other organs. Nevertheless, our findings are consistent with the recent reports on mitochondrial disturbances in those with trisomy 21 [19][20][21][22][23]. Decreased basal 3'-5'-cyclic adenosine monophosphate, increased reactive oxygen species and impaired NADH:ubiquinone reductase (complex I of the respiratory chain) were noted in fibroblasts from those with trisomy 21 [20].…”
Section: Discussionsupporting
confidence: 93%
“…We have recently demonstrated that FRAAs during gestation may play a role in thyroid abnormalities present in children with ASD [67]. Furthermore, genetic syndromes associated with ASD future science group www.futuremedicine.com such as Rett syndrome [68][69][70] and Down syndrome [71,72] demonstrate abnormalities in folate metabolism. Thus, a better understanding of how to identify and treat folate pathway abnormalities could have a significant impact in ASD and other neurodevelopmental disorders.…”
Section: Future Perspectivementioning
confidence: 99%